EFFECT OF WHITE FLOWERS OF Chrysanthmum CineraiaefoliumPLANT EXTRACT ON Tribolium Castanum - Mohammed, Ali (Iraqi Journal of Science, 2024)
The production , purification and determination of (Pyrethrin I, II) from the whiteflowers of Chrysanthemum cineraiaefolium plant were performed. The resultsobtained was (450 ml) as concentrated crude extract from using (25gm) powderedflowers dissolved in (1300ml) hexane. This extract was divided in to three parts, thefirst part (A) was the concentrated crude extract which have the yellow-greenishcolour, sticky and sharp odder, while the second part (B) was the (A) extractdissolved in (methanol 80%) which have pale – yellow colure and the third part (C)was the (B) extract with the activated charcoal, which was colourless extract. Theresults of HPLC analysis for determination, purification and quantity assessment forthe three parts (A, B, C) were (73.33 %, 77.33 %, 91.41 % ) respectively, and the concentration rate of (Pyrethrin I) to (Pyrethrin II) reached nearly (70 and 30)respectively for the (A, B, C) extracts. The biological activity test for the twocompound mentioned above was carried out as insecticide for repellence and killingthe flour beetles during different times (minutes) of treatment, using seven differentconcentrations of this extracts. The results obtained show that when increasing ofthe concentration and the time of treatment, the killing percentage was increased,such as in the concentration { (1: 0.5) – (crude : alcohol) } during (10 minutes) was98 % while, after (20 min) became 100%.